Bioassay of Recombinant Human Granulocyte Colony Stimulating Factor (rhG-CSF) for Neutropenia Treatment in Male Sprague Dawley Rats - Riyona Desvy Pratiwi; Dian Fitria Agustiyanti; Tri Isyani Tungga Dewi; Nina Herlina; Kartika Sari Dewi; Yuliawati Yuliawati; Aminah Aminah; Asrul Muhamad Fuad (Cell and BioPharmaceutical Institute, 2020)
Background: Recombinant human granulocyte colony stimulating factor (rhG-CSF) is a first line therapy for neutropenia. However, it is less affordable for most patients in developing and poor countries. Therefore, biosimilar products are developed to suppress the cost of treatment, namely with rhG-CSF. This study aimed to explore the establishment of an affordable rhG-CSF that has similar potential to induce neutrophils recovery as the positive control.Materials and Methods: The rhG-CSF was expressed as inclusion body in Escherichia coli NiCo21(DE3). The inclusion body was then solubilized, refolded, purified and characterized prior to be used in the bioactivity assay. Cyclophosphamide-induced male Sprague Dawley rats were used as animal model and administered with rhG-CSF. Blood sample was collected at several points of time, before and after rhG-CSF treatments. Complete blood count and peripheral blood smear were conducted to investigate the activity of the rhG-CSF on each blood cells type, particularly neutrophil.Results: Specific activity on neutrophil proliferation was shown after treatments with our rhG-CSF and positive control. Positive control dose 40 mg/kg BW was statistically similar with that of the rhG-CSF dose 80 and 120 mg/kg BW. However, in neutropenic condition, recovery of neutrophil counts could not be achieved within 4 days of treatments. Thus, a longer treatment is needed to observe the activity of the rhG-CSF as an antineutropenia agent.Conclusion: The rhG-CSF has been proven having specific activity on neutrophil proliferation. However, improvement in the rhG-CSF preparation is still needed and longer administration of the rhG-CSF has to be applied in the future study.Keywords: rhG-CSF, biosimilar, neutropenia, Sprague Dawley rats